The Relationship Between Loneliness and the COVID-19 Pandemic on Cognition and Well-Being in Older Adults. (17th December 2021) - Barber, Justin; Gibson, Allison; Bardach, Shoshana; Parsons, Kelly; Johnson, Julia; Jicha, Gregory; Rhodus, Elizabeth
Abstract: Social distancing is necessary to limit the spread of Covid-19. However, many older adults are predisposed to isolation and loneliness despite calls to socially distance. The current study examined loneliness during Covid-19 in relation to cognition and wellbeing in older adults. Data were extracted from a U.S. ADRC longitudinal study of aging database. Cognition was assessed using the NACC UDS 3.0 battery. Measures of well-being include: Short Form Health Survey, Subjective Memory Assessment, and Geriatric Depression Scale. Measurement of loneliness was selected from the NIH ADRC Covid-19 questionnaire. Data were from 115 older adults with normal cognition or MCI with a visit ≤18 months before research stoppage in March 2020 and after resumption in late-June 2020. Cognition and wellbeing are compared before and after onset of pandemic. Isolation due to Covid-19 may have long-term implications. Results of this study will highlight the need for acute assessments and psychosocial interventions.